Phenomenology and the social context of psychiatry: social relations, psychopathology, and Husserl's philosophy - Englander, Magnus (Bloomsbury studies in continental philosophy, 2017)
"Exploring phenomenological philosophy as it relates to psychiatry and the social world, this book establishes a common language between psychiatrists, anti-psychiatrists, psychologists and social workers. Phenomenology and the Social Context of Psychiatry is an inter-disciplinary work by phenomenological philosophers, psychiatrists, and psychologists to discover the essence and foundations of social psychiatry. Using the phenomenology of Husserl as a point of departure, the meanings of empathy, interpersonal understanding, we-intentionality, ethics, citizenship and social inclusion are investigated in relation to psychopathology, nosology, and clinical research. This work, drawing upon the rich classical and contemporary phenomenological tradition, touching on a broad range of thinkers such as Deleuze, Levinas, and R.D. Laing, also explicates how phenomenology is a method capable of capturing the human condition and its intricate relation to the social world and mental illness."--Bloomsbury Publishing